2023
DOI: 10.4018/978-1-6684-7689-5.ch009
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behaviour of Metallic Biomaterials in Physiological Environments

Abstract: Metals are often used in a wide range of biomedical applications since they have good mechanical characteristics, like higher strength, ductility, and toughness. However, the primary disadvantage of metallic biomaterials is their rapid reactivity, which causes corrosion when exposed to physiological conditions like body fluids. When exposed to body fluids, the metallic biomaterial is subjected to wear and corrosion; hence, the mechanical properties are reduced. Corrosion resistance, which also has a significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 89 publications
0
1
0
Order By: Relevance
“…These disadvantages have prompted researchers to consider using metals with sufficient mechanical properties and flexible design options [ 8 ]. Despite the potential benefits of bioactive metals like titanium and their alloys in binding to bones spontaneously, their use in artificial joints is limited by the potential for corrosion and wear [ 9 ]. Studies have shown that corrosion and wear in metallic joints can negatively impact their durability and reliability [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…These disadvantages have prompted researchers to consider using metals with sufficient mechanical properties and flexible design options [ 8 ]. Despite the potential benefits of bioactive metals like titanium and their alloys in binding to bones spontaneously, their use in artificial joints is limited by the potential for corrosion and wear [ 9 ]. Studies have shown that corrosion and wear in metallic joints can negatively impact their durability and reliability [ 10 ].…”
Section: Introductionmentioning
confidence: 99%